Examining Human Rights Derogation in State Emergencies - Phan, Huong Thi Lan; Doan, Kien Trung (Journal of Southeast Asian Human Rights, 2024)
Safeguarding human rights is the obligation of every nation under international human rights laws. However, some situations require a nation to restrict individual rights to protect public interests. Responding to COVID-19 provided a great example for Vietnam to review its legal ground for regulating limitations on human rights to prevent its expansion. However, the question remains: what are the legal grounds for executive agencies to limit citizens’ rights under the international standards on human rights protection? These precautionary measures support the prevention of the risks and damage caused by illegal acts or emergency cases, such as national disasters. Vietnam encounters legal issues, including the absence of comprehensive legal frameworks and delegating legislative authority during state emergencies. It also encounters inefficient mechanisms for reviewing the rationality and viability of preventive measures imposed by executive bodies. Consequently, safeguarding human rights according to international norms poses a significant challenge. This study explores Vietnam's solutions for handling the COVID-19 pandemic and suggests reforms to the country's legal framework regarding preventive measures. Keywords: State Emergency, Enforcement Measures, Legal Issues, Derogation of Human Rights, Vietnam